2019
DOI: 10.1097/sla.0000000000002790
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Obstruction and Ventral Hernia After Laparoscopic Versus Open Surgery for Rectal Cancer in A Randomized Trial (COLOR II)

Abstract: Based on long-term morbidity outcomes, laparoscopic surgery for rectal cancer could be considered a routine technique as there are no differences with open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 24 publications
1
28
0
4
Order By: Relevance
“…The aspect of long-term morbidity such as bowel obstruction and incisional and parastomal hernias within 5 years was examined in the COLOR II study, with the conclusion that both open and laparoscopic surgery deliver similar results [38]. The CLASSIC study trial (2005) reported increased positive circumferential resection margins (CRM) for laparoscopic anterior resections in rectal cancer patients compared to the open approach (12.4 vs. 6.3%) [39].…”
Section: Discussionmentioning
confidence: 99%
“…The aspect of long-term morbidity such as bowel obstruction and incisional and parastomal hernias within 5 years was examined in the COLOR II study, with the conclusion that both open and laparoscopic surgery deliver similar results [38]. The CLASSIC study trial (2005) reported increased positive circumferential resection margins (CRM) for laparoscopic anterior resections in rectal cancer patients compared to the open approach (12.4 vs. 6.3%) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Связано это с улучшением восстановления пациентов непосредственно после операции и сопоставимыми отдаленными результатами лечения [1]. С другой стороны, при анализе больших объемов данных было установлено, что нет достоверного различия в частоте образования послеоперационных грыж в 5-летней перспективе у пациентов с лапароскопическими и открытыми резекциями (3,9 %; 95 % доверительный интервал (ДИ) 3,3-4,4 и 4,1 %; 95 % ДИ 3,5-4,6), а при лапароскопическом доступе даже в 2,3 раза повышалась опасность гернио-пластики по экстренным показаниям (отношение рисков (ОР) 2,37; 95 % ДИ 1,03-5,46; p = 0,042) [4,5]. Это подтверждают выводы крупного метаанализа 6 рандомизированных контролируемых и 9 сравнительных исследований (в общей сложности 84 172 пациентов), где в целом после лапароскопической хирургии было меньше шансов на развитие послеоперационной грыжи и спаечной кишечной непроходимости, но при этом потребность в герниопластике либо хирургическом лечении спаечной непроходимости была такая же, как и у пациентов после открытых операций [6].…”
Section: материалы и методыunclassified
“…Несколько чаще ОКН встречается у мужчин (55%) и реже у женщин (45%). В большей степени подвержены риску развития ОКН пожилые люди и лица, которым проведены оперативные вмешательства на кишечнике и желудке [2]. Частота заболеваний острой кишечной непроходимостью относительно невелика и составляет по различным данным от 4 до 20 случаев на 100000 населения.…”
Section: Anesthetized Animals Were Used To Model Different Pathophysiunclassified